Influência da suplementação de diferentes ácidos graxos sobre o fotodano da pele induzido pela exposição de roedores à radiação ultravioleta - Barcelos, Raquel Cristine Silva (2014)
Diet fatty acids (FA) are fundamental to the phospholipids structure and function of cell membranes, in which long chain polyunsaturated FA (PUFA) increase its fluidity, while the trans FA (TFA) to make it more rigid. Also, the barrier function and hydration are highly dependent on the skin composition and structure, as well as the organization of lipids in the cell matrix. In recent years, the ozone layer depletion has increased human exposure to ultraviolet radiation (UVR), inducing deleterious effects on skin homeostasis. Moreover, lifestyle habits and eating patterns, especially in Western countries, has shown an increasing consumption of processed foods rich in AGT, whose cutaneous consequences do not present scientific validation. Whereas the skin health is partially related to the lipids that compose it, this study was designed to evaluate the effect of supplementation of different oils or fat in distinctlife periods of rodents on oxidative damage acute and chronic exposure to UVR-induced. Male Swiss mice weanling were supplemented daily (3g/kg, po) with soybean oil (C-SO; rich in n-6 PUFA), fish oil (FO; rich in n-3 PUFA) or hydrogenated vegetable fat (HVF; rich in TFA) until 90 days old and the dorsal skin was acutely exposed to UVR. The FO supplementation showed n-3 PUFA incorporation in mice skin, while the groups supplemented with soybean oil and HVF showed incorporation of n-6 PUFA and TFA, respectively. Such skin incorporations exerted influences on the development of UVR -induced oxidative damage in the mice skin and HVF group showed the highest protein carbonylation (PC) levels and lipid peroxidation, accompanied by larger skin thickening (edema), lower catalase (CAT) activity and cell survival. While soybean oil was associated with a partial prevention of damage observed in HVF group, FO supplementation prevented cutaneous oxidative damage UVR-induced. Sequentially, second and third experimental protocols were developed with the first and second generations offsprings born adult rats under daily supplementation of the same oils used in experiment 1 (SO, FO and HVF) and at 90 days old, each experimental group were exposed to UVR 3x/ week for 12 weeks. Animals first generation offspring (experiment 2) FO supplemented treated showed higher incorporation of n-3 FA and lower n-6/n-3 ratio in the dorsal skin, while the HVF group showed greater incorporation of TFA. Biochemical analyzes showed higher PC levels, per se, and smaller functionality of mitochondrial enzymes and decrease of some antioxidant defenses ((reduced glutathione (GSH) and vitamin C (VIT C)) in the dorsal skin HVF supplemented group. After UVR exposure, the same experimental group showed higher wrinkles scores, increased reactive species (RS) generation and PC levels, which were accompanied by decrease in GSH and VIT C skin levels. In contrast, FO group showed lower wrinkles scores and skin thickening after UVR exposure, besides lower PC levels and increased of the functionality of mitochondrial enzymes. Additionally, we observed a positive correlation between the RS generation-UVR induced and skin thickness, wrinkles and PC levels, while a negative correlation between the RS generation-UVR induced and functionality of mitochondrial enzymes, and between PC levels and GSH, SOD and VIT C.Animals of the second generation offspring (experiment 3) supplemented with FO showed higher n-3 FA incorporation and lower n-6/n-3 ratio in the dorsal skin, while TFA were incorporated only in HVF group. The latter experimental group showed biochemical changes per se: high RS generation, lower functionality of mitochondrial enzymes and increased Na+K+-ATPase activity. UVR exposure increased skin wrinkling andRS generation, besides reduced functionality of mitochondrial enzymes and GSH levels in HFV group. FO groupUVR exposure showed reduced skin thickness and PC levels, besides increase CAT activity and the preservation of Na+K+-ATPase activity. Whereas the n-3 PUFA compete with n-6 PUFA for desaturases and elongases activities, which originate from long chain n-3 or n-6 PUFA, respectively, which are incorporated into the cell membranesphospholipids.Such incorporation allows the cyclooxygenase-2 (COX-2) activity over them, originating active metabolites of the series 3 (prostaglandins (PG) and thromboxanes (TX)) or series 2 (PG and TX series 2), respectively. Series 3 metabolites are less pro-inflammatory than those of series 2, which may partly explain our findings. Moreover, to date, no study has shown the metabolites generation of AGT, even their influence on inflammation and pro-oxidant in cell membranes. How TFA have been reported to inhibit the desaturases activity, we suggest that the presence of AGT in the membranes may be inhibiting the n-3 PUFA incorporation and, thus, reduce the metabolites generation, which are known to be beneficial. Taken together, the data presented in this thesis suggest that healthy eating habits that include reduced intake of foods rich in AGT and the inclusion of n-3 PUFA, accompanied by care front sun exposure can contribute to the prevention of skin diseases and skin diseases associated with UV exposure.